Studi Deskriptif Bentuk-bentuk dan Penyebab Terjadinya Bullying di Kelas V SDN 60 Kota Bengkulu - Feridian Pribowo; Osa Juarsa; Nani Yuliantini (Universitas Bengkulu, 2023)
This study aims to describe the forms of bullying in class V of SDN 60 Kota Bengkulu. The method and type of research used in this study is qualitative descriptive. The research subjects were fifth grade students of SDN 60 Kota Bengkulu. The technique of collecting data uses observation and interviews. Data analysis is done by collecting data (data collection), data reduction (data reduction), presenting data (display data) and drawing conclusions (Verification data). Testing the validity of the data using an extension of observation, increasing perseverance, and data triangulation. Based on the results of the study, it can be concluded that the behavioral forms and causes of bullying that occur in SDN 60 Kota Bengkulu, Types of bullying include physical bullying, verbal bullying, and psychic bullying: (1) Physical bullying includes: pushing, hitting, kicking, bullying , and damaging other people's goods, verbal bullying includes: spreading news incorrectly, bestowing mistakes on others, mocking, dubbing friends with animal names, and bullying friends, psychic bullying includes: Students do not care about other students, discriminate against other students and demean other students, (2) The causes of bullying include family factors, bad individual factors, and school factors: Family factors include: lack of communication between parents and children and children who lose their father / mother, bad individual factors including : seeking popularity / attention, and revenge / jealousy, the School factor is the lack of teacher supervision.